O uso do nome social como estratégia de inclusão escolar de transexuais e travestis - Lima, Maria Lúcia Chaves (2013)
In 2008, the Government of Pará authorized transvestites and transsexuals to use their social names at public schools. Focusing on this event, we grounded on theories developed by the philosopher Michel Foucault to examine the effects of social name policy as a strategy for school inclusion of travestities and transsexuals. We describe life stories of eight travestites/transsexuals interviewed, and also present pieces of information produced in various situations, to problematize the government of transvestites and transsexuals through inclusion policy. To build the field in which this study is situated, we discuss how knowledge of transvestites and transsexuals experiences are fabricated as a problem. The ministerial order that establishes the social name is, as well, understood as a governamentality strategy and we give visibility to their elaboration process as well as oppositions and difficulties faced in implementation process. Finally, we present the effects of this legislation. These effects are not reducible to the desired insertion of the target public at schools because they also cover their potential to produce modes of subjectification. We intend to demonstrate that such policy creates tension zones between normalization strategies of modes of living and practice of resistance. It is argued that educational inclusion of diverse modes of living depends on multiple factors, and inclusion policies are only one of these many aspects